Patterns of CRISPR/Cas9 activity in plants, animals and microbes. Issue 12 (11th October 2016) - Bortesi, Luisa; Zhu, Changfu; Zischewski, Julia; Perez, Lucia; Bassié, Ludovic; Nadi, Riad; Forni, Giobbe; Lade, Sarah Boyd; Soto, Erika; Jin, Xin; Medina, Vicente; Villorbina, Gemma; et al.
Summary: The CRISPR/Cas9 system and related RNA‐guided endonucleases can introduce double‐strand breaks (DSBs) at specific sites in the genome, allowing the generation of targeted mutations in one or more genes as well as more complex genomic rearrangements. Modifications of the canonical CRISPR/Cas9 system from Streptococcus pyogenes and the introduction of related systems from other bacteria have increased the diversity of genomic sites that can be targeted, providing greater control over the resolution of DSBs, the targeting efficiency (frequency of on‐target mutations), the targeting accuracy (likelihood of off‐target mutations) and the type of mutations that are induced. Although much is now known about the principles of CRISPR/Cas9 genome editing, the likelihood of different outcomes is species‐dependent and there have been few comparative studies looking at the basis of such diversity. Here we critically analyse the activity of CRISPR/Cas9 and related systems in different plant species and compare the outcomes in animals and microbes to draw broad conclusions about the design principles required for effective genome editing in different organisms. These principles will be important for the commercial development of crops, farm animals, animal disease models and novel microbial strains using CRISPR/Cas9 and other genome‐editing tools.